The Role Of Gender Diversity In Increasing ESG Performance Through Intellectual Capital - Isnindiah Sofiati; Aria Farah Mita (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2024)
This study examines whether intellectual capital mediates the association between board gender diversity and ESG performance. The samples were selected based on criteria that included all non-financial companies registered on the Indonesia Stock Exchange. The total observations are 257 in the period 2017 to 2022. ESG scores were obtained from the Refinitiv Eikon database as a proxy for ESG performance, intellectual capital proxied by the value-added intellectual coefficient (VAIC) model, and directors' gender diversity proxied by the percentage of female directors. The results show intellectual capital mediates the association between board gender diversity and ESG performance. These results suggest that board gender diversity positively affects ESG performance if the company has intellectual capital that adds value to create competitiveness. This study aims to help companies understand the importance of gender diversity in managing and utilising intellectual capital to improve the company's ESG performance.